PENGARUH PENERAPAN LAYANAN SAMSAT KELILING, E-SAMSAT DAN SAMSAT DRIVE - THRU TERHADAP PENERIMAAN PAJAK KENDARAAN BERMOTOR DI KABUPATEN BULELENG - Atmaja, I Nyoman Satria Wira; Wahyuni, Made Arie (Vokasi : Jurnal Riset Akuntansi, 2025)
This research aims to analyze the impact of the implementation of MobilE Samsat services, E-Samsat, and Drive-thru Samsat on the revenue from Motor Vehicle Tax (PKB) in Buleleng Regency. The background of this research is based on the low realization of motor vehicle tax revenue compared to the set target, despite the availability of various innovative tax payment services. This study uses a quantitative approach with multiple linear regression analysis methods. Data was collected through distributing questionnaires to taxpayers and documentation from the Regional Tax and Retribution Service Office of Bali Province in Buleleng Regency.The research results show that both partially and simultaneously, mobile Samsat services, E-Samsat, and Samsat Drive-thru have a positive and significant impact on the acceptance of motor vehicle tax (PKB). This finding supports the Unified Theory of Acceptance and Use of Technology (UTAUT) which explains that the adoption of technology and service convenience encourages an increase in taxpayer compliance. This research is expected to provide input for Samsat managers in improving service quality to optimize PKB collection.